Greetings from witness protection! - Burt, Jake (Feiwel and Friends, 2017)
Thirteen-year-old Nikki Demere is an orphan and a kleptomaniac, making her the perfect girl to portray the Trevors' daughter in witness protection, but she soon learns that the biggest threat to her new family's security comes from her own past.